2022
DOI: 10.34133/2022/9832128
|View full text |Cite
|
Sign up to set email alerts
|

CNS Organoid Surpasses Cell-Laden Microgel Assembly to Promote Spinal Cord Injury Repair

Abstract: The choice of therapeutic agents remains an unsolved issue in the repair of spinal cord injury. In this work, various agents and configurations were investigated and compared for their performance in promoting nerve regeneration, including bead assembly and bulk gel of collagen and Matrigel, under acellular and cell-laden conditions, and cerebral organoid (CO) as the in vitro preorganized agent. First, in Matrigel-based agents and the CO transplantations, the recipient animal gained more axon regeneration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Matrigel, gelatin, fibronectin, and laminin are possible culture substrates for neural cells (Komura et al 2015 ). Matrigel is a gelatinous, high in various CNS proteins extracellular matrix mixture secreted by Engelbreth-Holm-Swarm mouse sarcoma cells (Berg et al 2018 ; Wang et al 2022 ). This substrate promotes the differentiation of various cell types (Kleinman and Martin 2005 ).…”
Section: In Vitro Bbb Modelsmentioning
confidence: 99%
“…Matrigel, gelatin, fibronectin, and laminin are possible culture substrates for neural cells (Komura et al 2015 ). Matrigel is a gelatinous, high in various CNS proteins extracellular matrix mixture secreted by Engelbreth-Holm-Swarm mouse sarcoma cells (Berg et al 2018 ; Wang et al 2022 ). This substrate promotes the differentiation of various cell types (Kleinman and Martin 2005 ).…”
Section: In Vitro Bbb Modelsmentioning
confidence: 99%
“…After 14 d of in vitro culturing, the SCLT exhibited architectural and phenotypic changes in the adult rat's spinal cord, and significant motor function recovery was achieved after the transplantation of SCLT into the rat SCI model [17]. Furthermore, Wang et al reported that the transplantation of pre-matured cerebral organoids facilitated spinal cord regeneration in SCI [18]. These collective research works indicate that the pre-maturing of NSCs before transplantation can increase neuronal phenotypes and generate better functionality, thus ultimately promoting regeneration effect in vivo.…”
Section: Introductionmentioning
confidence: 99%